2019
DOI: 10.3389/fpls.2019.00828
|View full text |Cite
|
Sign up to set email alerts
|

Coumarin-Induced Delay of Rice Seed Germination Is Mediated by Suppression of Abscisic Acid Catabolism and Reactive Oxygen Species Production

Abstract: Abscisic acid (ABA) is a crucial phytohormone for the regulation of seed germination. The ABA content of seeds is regulated by synthesis and catabolic pathways. Coumarin, an important plant allelochemical, can inhibit seed germination effectively, although whether it is involved in the regulation of ABA content during seed germination has not been elucidated. For the study reported herein, we show that coumarin effectively inhibits rice seed germination and vivipary. We found that the ABA content gradually dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 46 publications
1
23
0
1
Order By: Relevance
“…Recently coumarin, which has been reported to play a role in allelopathic interactions, was also shown to inhibit rice seed germination by suppressing ABA catabolism and promoting ROS accumulation (Chen et al, 2019). Additionally, seed storage protein mobilization, a process regulated by ABA, has been shown to be impaired in response to MB treatment in germinating seeds , suggesting that ABA may be involved in the MB-mediated inhibition of seed germination.…”
Section: Discussionmentioning
confidence: 99%
“…Recently coumarin, which has been reported to play a role in allelopathic interactions, was also shown to inhibit rice seed germination by suppressing ABA catabolism and promoting ROS accumulation (Chen et al, 2019). Additionally, seed storage protein mobilization, a process regulated by ABA, has been shown to be impaired in response to MB treatment in germinating seeds , suggesting that ABA may be involved in the MB-mediated inhibition of seed germination.…”
Section: Discussionmentioning
confidence: 99%
“…Coumarin’s phytotoxicity and its ability to alter both root anatomy and morphology have been primarily documented [ 12 , 50 ]. Previous studies have demonstrated that this molecule is a potent inhibitor of germination and seedling growth and development [ 51 , 52 ]. On the contrary, at relatively low concentrations (100 µM), it significantly stimulates lateral root and root hair production, whereas the total root length is significantly reduced [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, as ROS production is prevented by inhibitors such as diphenylene iodonium chloride, adenine, SDIC among others, seed germination is also delayed (Müller et al, 2009; Zhang et al, 2014a). Previously, we found that coumarin inhibits rice germination by suppressing ABA catabolism (Chen et al, 2019).…”
Section: Introductionmentioning
confidence: 95%